Impact of aromatic residues on the intrinsic disorder and transitional behaviour of model IDPs. (December 2022) - García-Arévalo, C.; Quintanilla-Sierra, L.; Santos, M.; Ferrero, S.; Acosta, S.; Rodríguez-Cabello, J.C.
Abstract: Understanding the interplay between order and disorder in intrinsically disorder proteins (IDPs), and its impact on the properties and features of materials manufactured from them, is a major challenge in the design of protein-based synthetic polymers intended for advanced functions. In this paper an elastin-like diblock co-recombinamer amphiphile (Phe-ELR) based on a hydrophobic block containing five phenylalanine (Phe) residues proximal to the carboxyl function of a glutamic acid (Glu) residue upon folding, and with Glu as the guest residue in the hydrophilic part, was engineered and its assembly behaviour compared with another amphiphilic ELR used as control. Phe-ELR was tailored in order to clarify the impact of the presence of aromatic residues in the amino acid sequence, which even in early studies by Urry's group already demonstrated a certain out-of-trend behaviour compared with other apolar amino acids, especially non-aromatic ones, on ELR behaviour. The combination of several experimental techniques indicates strong molecular interactions associated with the Phe residue, thus resulting in limited reversible character of the temperature-induced transitions during sequential thermal cycles, a lower than expected transition enthalpy, and clear differences in its supramolecular assembly with respect to the control ELR. A distinctive pre-aggregated state for the Phe-ELR under any condition of pH and temperature is found. Eventually, this state gives rise to Phe-core micelles or a solid jelly-like material, depending on the concentration, pH and presence of salts. In conclusion, it appears that the presence of aromatic residues and their ability to promote strong inter- and intramolecular interactions at any temperature and pH causes a complete modification of the order-disorder interplay present in other, non-aromatic ELRs. These molecular events have a profound impact on the physical properties of the resulting polymer when compared with other ELRs. This work helps to shed light on the limits that govern intrinsic disorder in ELRs beyond its inverse temperature transition. Graphical abstract: Image 1